(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describes the current situation and identifies some factors related to the knowledge and care practices of mothers with children under 5 years old suffering from otitis media at Gia Dinh General Hospital. Subjects and methods: A cross-sectional descriptive study was conducted at Family General Hospital from March 2025 to April 2025 on 76 mothers with children under 5 years old suffering from otitis media. Results: 64,5% of mothers demonstrated adequate knowledge and 42,1% demonstrated adequate practices regarding the care of children under five years old with otitis media. Factors related to mothers’ knowledge included: educational level and occupation. Factors related to mothers’ practices included: educational level, occupation, and knowledge. The group with higher educational levels showed greater levels of both knowledge and practice. The percentage of mothers with adequate knowledge and practice was 59.2%, higher than the group with inadequate knowledge. The difference was statistically significant with p<0.05. Conclusion: Mothers with children under 5 years old suffering from otitis media have limited knowledge and practices. Therefore, intervention programs are necessary to improve mothers’ knowledge and practices in this area.